MENGULAS BOARDGAME “SI ANAK NAKAL” DENGAN MODEL INTERAKSI ANALISIS - Emmareta Fauziah; Achmad Sultoni (Universitas Mercu Buana, 2021)
More than 7 hours a day Generation Z interacts with devices, so less time is spent interacting directly with humans their age. This type of boardgame is a game that increases the interaction between players. To develop a board game, it is necessary to know the aspects and components contained in it. In the last few years, there have been boardgames featuring local fairy tales, one of which is “Si Anak Nakal” by Mahavira Studio. This game research has been carried out previously by Kelvin and Hantanto in 2019 entitled